Probabilistic Health Risk Assessment Due to Natural Formaldehyde Intake Through Opah Fish (Lampris Guttatus) Consumption in Indonesia - Ajeng Kurniasari Putri; Umi Anissah; Farida Ariyani; Singgih Wibowo (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2018)
Opah fish (Lampris guttatus) is one of the bycatch products of Tuna fish catch. The fish currently has become one of the major exported commodities of Indonesia. However, due to its natural deterioration, the fish contained high formaldehyde up to 200 ppm which can be one of health risk when consumed. The aim of this study is to obtain probabilistic health risk assessment data due to consumption of opah fish that contaminated with natural formaldehyde. The study was initiated with analyzing the formaldehyde content of the opah fish (Lampris guttatus) stored in freezing temperature for less than three months. To evaluate the population risk associated with consumption of formaldehyde-contaminated fish, a probabilistic exposure assessment was conducted in several categories based on individual characters who are likely to consume opah fish. Exposures are grouped by sex (male and female) and age (children and adults). To identify the best fit distribution in the probabilistic exposure analysis, fish consumption, body weight and natural occurrence of formaldehyde concentration in Opah fish were fitted in the @Risk®7.0 for Microsoft Excel 2010. Risk exposure analysis was conducted based on the formaldehyde content in Opah fish (real concentration) and two other scenarios of  2 and 4 times of the Opah fish real formaldehyde content. The result showed that Opah fish caught in Indonesian waters and stored in freezing temperature for less than three months, due to deterioration process, could naturally produce formaldehyde ranged from 4,62 ± 0,00 mg/kg to 58,10 ± 0,46 mg/kg. Consequently, based on the probabilistic exposure assessment, female children in Jakarta and Surabaya were considered as in health risk problems. Extremely, the further simulations using two and four times of formaldehyde concentration exposure revealed the health risk  for both gender and all age groups  of Jakarta and Surabaya residents. Therefore, the stakeholders i.e. government and policy makers should take some priorities in formulating a proper risk management strategy on the basis of knowledge of endogenous formaldehyde present in Opah fish as well as risk management strategies for the fish consumer in Indonesia.